2020
DOI: 10.1534/genetics.119.302754
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inbreeding: Genetic Crosses Drive Apparent Adaptive Mutation in the Cairns-Foster System ofEscherichia coli

Abstract: The Escherichia coli system of Cairns and Foster employs a lac frameshift mutation that reverts rarely (10−9/cell/division) during unrestricted growth. However, when 108 cells are plated on lactose medium, the nongrowing lawn produces ∼50 Lac+ revertant colonies that accumulate linearly with time over 5 days. Revertants carry very few associated mutations. This behavior has been attributed to an evolved mechanism (“adaptive mutation” or “stress-induced mutagenesis”) that responds to starvation by preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This mutagenesis, which seems to be restricted to plasmid genomes, occurs through an increase in PCN in a subpopulation of cells. Conjugative transfer of these plasmids between clone mates further amplifies plasmid genomes, which are then subject to extensive mutagenesis mediated by the plasmid-encoded, error-prone polymerase DinB 47,112 .…”
Section: [H1] Further Plasmid Effects On Evolutionmentioning
confidence: 99%
“…This mutagenesis, which seems to be restricted to plasmid genomes, occurs through an increase in PCN in a subpopulation of cells. Conjugative transfer of these plasmids between clone mates further amplifies plasmid genomes, which are then subject to extensive mutagenesis mediated by the plasmid-encoded, error-prone polymerase DinB 47,112 .…”
Section: [H1] Further Plasmid Effects On Evolutionmentioning
confidence: 99%
“…Most studies of directed adaptive mutation, which remains a highly controversial concept (for example, see ref. 18 ), have been performed in Escherichia coli , but additional studies have been reported in other bacteria and eukaryotes, including yeast and mammals 17 , 19 , 20 . While there is no consensus regarding whether directed mutation can occur, there is a range of reported evidence for stress-induced hypermutation, which can increase the probability of creating favorable mutations that can be acted upon by natural selection 21 .…”
Section: Second-line Adaptive Mechanismsmentioning
confidence: 99%
“…This is well illustrated by the plasmid-mediated spread of genes responsible for antimicrobial resistance, virulence factors and the ability to degrade xenobiotics (Heuer & Smalla, 2012). Other plasmid accessory genes may promote bacterial adaptation by enhancing mutagenesis instead, an effect that has been linked to plasmid-encoded error-prone polymerases (Woodgate & Sedgwick, 1992; Remigi et al, 2014; Sano et al, 2014; Nguyen et al, 2020). Although plasmids confer new phenotypes directly associated to the accessory genes they encode, they may also collaterally manipulate host behaviour via regulatory cross-talks, which result in the indirect expression of further phenotypic variation (Billane et al, 2021) [e.g., altered host metabolism (Hall et al, 2024)].…”
Section: Introductionmentioning
confidence: 99%